Transforming Kenya’s addressing landscape: use case models approach to a responsive National Addressing System - Kipkemoi, Isaac; Ngare, Innocent Osoro (Frontiers in Sustainable Cities, 2025)
The rapid urbanization and population growth in Kenya highlight the need to revive the National Addressing System (NAS). This study aims to examine address systems across the globe, focusing on countries known for their efficient addressing infrastructures, such as the USA, UK, Japan, Switzerland, and Germany, and compare them to the currently used system in Kenya. Additionally, we critique the format proposed by NAS and use this knowledge to build conceptual models of a responsive NAS. Beyond conducting a simple survey of best practices, our objective is to extract the underlying principles and intricacies that lead to the success of these models. Drawing on this extensive global knowledge, our research aims to propose a detailed conceptual framework specifically designed to address the unique attributes and challenges that characterize Kenya’s dynamic addressing landscape. By combining global insights with local needs, this paper advocates for a NAS that goes beyond traditional boundaries, aligning with international standards while promoting adaptability and resilience in response to the ever-changing urban fabric of Kenya.